2014
DOI: 10.1186/1478-4491-12-45
|View full text |Cite
|
Sign up to set email alerts
|

Trends and implications for achieving VISION 2020 human resources for eye health targets in 16 countries of sub-Saharan Africa by the year 2020

Abstract: BackgroundDevelopment of human resources for eye health (HReH) is a major global eye health strategy to reduce the prevalence of avoidable visual impairment by the year 2020. Building on our previous analysis of current progress towards key HReH indicators and cataract surgery rates (CSRs), we predicted future indicator achievement among 16 countries of sub-Saharan Africa by 2020.MethodsSurgical and HReH data were collected from national eye care programme coordinators on six practitioner cadres: ophthalmologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 6 publications
2
33
0
Order By: Relevance
“…These include low rates of early detection and diagnosis,17 lack of specialist equipment and treatment options, lack of specialist glaucoma clinics and care pathways, poor compliance with treatment and follow-up,9 the high cost of accessing care and treatment costs18 and lack of awareness and public knowledge about glaucoma compounded by socioeconomic deprivation 10. The number of eye health workers in Nigeria, including ophthalmologists and optometrists, falls short of WHO recommendations 19 20. In addition, Nigeria does not have an eye health policy and the national strategic plan for eye care is not uniformly implemented.…”
Section: Glaucoma In Nigeriamentioning
confidence: 99%
“…These include low rates of early detection and diagnosis,17 lack of specialist equipment and treatment options, lack of specialist glaucoma clinics and care pathways, poor compliance with treatment and follow-up,9 the high cost of accessing care and treatment costs18 and lack of awareness and public knowledge about glaucoma compounded by socioeconomic deprivation 10. The number of eye health workers in Nigeria, including ophthalmologists and optometrists, falls short of WHO recommendations 19 20. In addition, Nigeria does not have an eye health policy and the national strategic plan for eye care is not uniformly implemented.…”
Section: Glaucoma In Nigeriamentioning
confidence: 99%
“…Recent studies of human resources in eye health in sub-Saharan Africa and Latin America have confirmed these trends of poor distribution and the inability of the cadre to keep up with the population rates. [4][5][6][7] Amidst technological advances, population demand patterns and evolving models of care, complete data for eye health professionals is an integral component to understanding if we can meet the needs of the global population.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients will be unable to undergo second implantation of IOL, as cost and transport duration pose a formidable barrier (32,33). Furthermore, there are often shortages of cataract surgeons, nurses and equipment in low-and middle-income countries, and the training of new cataract surgeons is not sufficient to meet demand (33,34). In addition, it is often difficult to access optometric services in such countries, therefore all patients following cataract surgery that are unable to undergo implantation, will experience reduced postoperative visual acuity (35).…”
Section: Discussionmentioning
confidence: 99%